2018
DOI: 10.1371/journal.pone.0202616
|View full text |Cite
|
Sign up to set email alerts
|

Quality circles for quality improvement in primary health care: Their origins, spread, effectiveness and lacunae– A scoping review

Abstract: Quality circles or peer review groups, and similar structured small groups of 6–12 health care professionals meet regularly across Europe to reflect on and improve their standard practice. There is debate over their effectiveness in primary health care, especially over their potential to change practitioners’ behaviour. Despite their popularity, we could not identify broad surveys of the literature on quality circles in a primary care context. Our scoping review was intended to identify possible definitions of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 110 publications
1
63
0
Order By: Relevance
“…Portugal’s primary care system has developed rapidly over the past few years, with a corresponding development in QCs. Similarly, the QC participation rate in France increased from ‘no QCs in existence’ in 2000 to involving at least 10% of GPs in 2015, as recorded in studies and numerous projects [1,26]. The reasons for different development patterns in different countries are not fully clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Portugal’s primary care system has developed rapidly over the past few years, with a corresponding development in QCs. Similarly, the QC participation rate in France increased from ‘no QCs in existence’ in 2000 to involving at least 10% of GPs in 2015, as recorded in studies and numerous projects [1,26]. The reasons for different development patterns in different countries are not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…QCs help participants link evidence to everyday practice, deal with uncertainty and feel secure in their professional roles. Participation may strengthen team-based strategies for preventing errors, reduce burnout, and help practices retain practitioners [1].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literatures suggest that the QCC used in health care is likely to be a powerful technique for facilitating high-quality healthcare and improved outcomes. [14][15][16][17][18][19] The study by Wang et al 14 reviewed the tangible and intangible achievements of 92 QCCs carried out in a medical institution in Zhejiang province. This study showed that QCCs improve performance indicators in terms of reducing costs and internal errors, and improving work quality, patient satisfaction and economic performance.…”
Section: The Status Of Qcc Activities In Hospitals In Mainland Chinamentioning
confidence: 99%
“…Small groups have been widely used as a learning format in medical CPD in central and northern continental Europe since the 1970s, [12][13][14][15] and later in Canada and Scotland, 16 and Ireland, 17 most commonly in primary care, but also in psychiatry in Europe 18 and Australia and New Zealand. Such groups are variously named and take a range of formats (see Table 1).…”
Section: Description Of Small Groups In Cpdmentioning
confidence: 99%